Hon var ändå läkare - Ingridsdotter, Jenny (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2017)
When initiating the work with my dissertation on postsocialist migration to Argentina I realised the two traditions that I had been trained in during my undergraduate years, the ethnological and the post-colonial, presented my with a dilemma. How was I to make sense out of the former Soviet life worlds the research participants had lived in and how could I, as a Western European, approach their experience in a tactful way without creating them as peculiar ”others” of the East? In this article I examine how fiction texts, and particularly the work of Svetlana Alexievich, helped me in that process. I propose that the reading and writing of fiction can be an important tool for ethnological scientific production, both in terms of planning for research but also in writing up the results. Comparisons are drawn between the methodology described by Alexievich for her work on the former Soviet and the present post-Soviet context. Her way of interviewing for the books resembles the ethnographic process, but in the end it is her literary fantasy and not scientific facts that decide the written outcome of the process. I suggest that besides engaging in the traditional channels for communicating research results, we also allow to think of alternative ways of writing up results, for example through literary or journalistic pieces. This might help us become better scientists as it helps us in regarding our empirical material in novel ways. This article is followed by a short story about a Russian woman in Buenos Aires. The content is based upon the empirical material for my dissertation, yet the way the woman tells her story and her emotions is my literary creation. I regard the process of writing short stories from the empirical material as a condensed form of analysing my material, similar to Alexievich’s methodology.